Insights into antiviral mechanisms of remdesivir, lopinavir/ritonavir and chloroquine/hydroxychloroquine affecting the new SARS-CoV-2 (2020)
Coronavirus disease 2019 (COVID-19) is a kind of viral pneumonia with an unusual outbreak in Wuhan, China, which is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). There is currently no licensed antiviral treatment available to prevent human CoV infection. The widespread clinical use and existing knowledge on antiviral mechanisms of remdesivir, lopinavir/ritonavir and chloroquine/hydroxychloroquine in the treatment of previous epidemic diseases, namely, severe acute respiratory syndrome (SARS) and Middle East respiratory syndrome (MERS), may be helpful in the combat with novel SARS-CoV-2 infection. Recent clinical evidence didn’t confirm the beneficial role of lopinavir/ritonavir and chloroquine/hydroxychloroquine for COVID-19 patients and their use was reassessed. We provide an overview of the current evidence into the mechanisms of action of these available drugs which are repurposed for treatment of the new virus. Available data identifies remdesivir as an adenosine analogue that can target the RNA-dependent RNA polymerase and block viral RNA synthesis. It has been a promising antiviral drug against a wide array of RNA viruses. 3CLpro is a major CoV protease that cleaves the large replicase polyproteins during viral replication and can be targeted by the protease inhibitor lopinavir/ritonavir but the clinical effects are controversial. Chloroquine/Hydroxychloroquine could impair the replication of SARSCoV-2 by multiple mechanisms and their immunomodulatory properties could ameliorate clinical manifestations that are mediated by immune reactions of the host although its beneficial effects are under question and need to be proven at the clinical level. Existing in vitro and in vivo evidence delineate the molecular mechanisms of these drugs in CoV-infected cells. Numerous studies demonstrated the ability of remdesivir to inhibit SARS-CoV-2 replication but future research would be needed to understand the exact mode of action of lopinavir/ritonavir and chloroquine/hydroxychloroquine in SARS-CoV-2 infected cells and to use this knowledge in the treatment of the current COVID-19.